Respuesta :
Part A: first multiply 2 by x and -3 → combine all like terms → Add 6 on both sides → subtract 6x from both sides.
Your final answer should be -5
step by step: 4x + 2(x-3) = 4x + 2x - 11
4x +2x -6 = 4x + 2x - 11
6x -6 = 6x - 11
6x = 6x -11 +6
6x = 6x -5
6x-6x= -5
0 = -5
Part B: Add all like terms.
Hope this helps! :)
There is NO SOLUTION. We used the distributive property to distribute the 2(x-3).
Explanation:
4x+2(x-3)=4x+2x-11
4x+2x-6=4x+2x-11 Distribute 2 by x-3
6x-6=6x-11 Combine Like Terms
-6=-11 Subtract Weaker X
-6≠-11 Find Answer
-6 does not equal -11, so there is no solution to this equation.
Explanation:
4x+2(x-3)=4x+2x-11
4x+2x-6=4x+2x-11 Distribute 2 by x-3
6x-6=6x-11 Combine Like Terms
-6=-11 Subtract Weaker X
-6≠-11 Find Answer
-6 does not equal -11, so there is no solution to this equation.